Studnets´ views on voluntary reading : Voices from Finnish and Georgian students, including ones with hearing impairments - Gviniashvili, Zhuzhuna (My University, 2020)
Although originally focused on the direct transmission of information for practical reasons, reading eventually greatly expanded to include a host of functions, including leisure activities. The Master Thesis in question tries to investigate students´ attitudes towards reading and their path from reading intention to actual reading. The study is focusing on the perspectives of Georgian and Finnish students, including the ones with hearing impairments. The mixed method of data collection and data analysis is applied. The choice of using combined methods is strongly related to the nature of research questions. The rate of students´ engagement in voluntary reading is numerical data; while the attitude towards reading are revealed through focus group interviews. Students regardless of the country and hearing impairments expressed a positive attitude towards reading. With the easiest words, we can interpret students´ general beliefs about reading as the best way to deepen knowledge and enrich experience. However, as revealed, the rate of actual reading is not as high as an intention to read; an utterly positive attitude towards voluntary reading unfortunately is not proportional to actual reading engagement. Among the most common impediment factors students in both countries nominated the long school days, large amount of homework, limited free time and modalities of leisure activities such as watching movies, internet surfing and video games. In the conclusion part of the thesis certain possible measures are discussed as humble suggestions to address and solve the problem of students´ poor engagement in voluntary reading.
Keywords: Keywords: reading, voluntary reading, reading for pleasure, impediment factors, hearing impairment, deaf, reading modalities.